Chemical Modification and Characterization of Starches from Soursop as Potential Water Based Drilling Fluid Additives - Adewumi, Chizoma Nwakego; Joy, James; Ogwuda, Uchechukwu Anthony; Ezebuiro, Victor (Journal of petroleum science and technology, 2024)
Starch reduces fluid loss while enhancing viscosity in drilling fluid formulation. Starch obtained from soursop (SS) was chemically modified by carboxymethylation methods (SC1 & SC2) and acetylation method (SA) and compared with cassava (CN). The physicochemical properties: swelling power, gelatinization temperature, thermal stability and particle size, rheological properties: yield point (YP), gel strength and plastic viscosity (PV) and also fluid loss control of the starches were investigated to determine their performance as viscosity enhancer and fluid loss control ability in drilling fluid. The results obtained revealed that modified starches (SC1 and SC2) demonstrated better physicochemical properties than SA, SS and CN. Thus, showing that carboxymethylation improved the thermal stability and gelatinization temperature of the starches. The morphology result revealed that modification reduced the particle size of the starches thereby, increasing their surface area and reactivity. In addition, the native and modified soursop starches exhibited good rheological properties and fluid loss control as required by API standards. However, modified starch, SC2 exhibited better rheological properties in PV, YP, gel strength and controlled filtration-loss than other starches SC1, SA as well as native soursop and cassava. The possession of these excellent properties places soursop and its modified starches (SCI and SC2) as potential replacement for cassava as additives in drilling fluid formulation. This will help improve efficiency in drilling operations, and on the other hand help to reduce the negative impact on food security in Nigeria since soursop is mainly consumed as a dessert.